Improving Quality of Life with Percutaneous Coronary Intervention in Chronic Coronary Syndrome Patients with SYNTAX Score of More than 22 - Wella Karolina; Mohammad Saifur Rohman; Pawik Supriadi; Djanggan Sargowo; Wira Kimahesa Anggoro; Yoga Waranugraha (Heart Science Journal, 2021)
Background: The benefit of PCI to improve quality of life (QoL) in chronic coronary syndrome (CCS) is still unclear Objectives: This study aimed to assess the benefit of percutaneous coronary intervention (PCI) in improving QoL among CCS patients receiving OMT.Methods: We conducted a retrospective cohort study. CCS patients who underwent coronary angiography (CAG) and/or PCI were grouped into OMT plus PCI and OMT groups. The SYNTAX score was used to assess the complexity and severity of coronary artery lesions. The outcome measured was QoL assessed using Seattle Angina Questionnaire (SAQ) and rehospitalization.Results: A total of 57 patients in the OMT plus PCI group and 49 patients in the OMT group were included. The percentage of patients with good QoL was higher in the OMT plus PCI group than OMT only group (64.5% vs. 35.5%; p = 0.007). The OMT plus PCI group revealed a better activities of daily living (85.11 ± 12.46 vs. 12.46 ± 21.87; p = 0.014) and angina stability (84.32 ± 23.63 vs. 71.81 ± 27.89; p = 0.014) than OMT group. Among patients with SYNTAX scores of more than 22, achievement of good QoL was greater in the OMT plus PCI group than the OMT group (80.8% vs. 45.5%; p = 0.025).Conclusion: PCI improved the QoL in CCS patients treated with OMT. Second, OMT plus PCI improves physical limitation and angina stability. For patients with a SYNTAX score of more than 22, OMT plus PCI was correlated with good QoL achievement